Genetic Relationship of Banana at Bandarlampung City Based on The Number of Chromosome and Genom Type - Eti Ernawiati; Martha L. Lande (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
A banana was rank 4th as food consumed by the world community after rice, wheat, and corn. Identification and characterization were important steps to explore the potential and important value of this plant. This study aims to obtain the kinship profile of banana germplasm in Bandarlampung City based on the number of chromosomes and their genome types. Characterization of banana accession is done by observing the morphological characteristics referring to 15 characters from Simmonds and Shepherd with the expected score of genomic determinants modified by Silayoi and Camchalow. The results of dendrogram analysis showed that on a scale of 20-23 obtained 2 groups of banana accessions. The first group consisted of 7 accessions of bananas, namely Kepok Kapas, Kepok Manado, Kepok Kuning, Rabig, Kepok Batu, Raja Sajen, and Pisang Batu. The second group consisted of 15 accessions, namely Kepok Abu, Horn, Thousand, Janten, Mas Kuning, Mas, Muli, Rejang, Ambon Lumut, Papan, Cavendish, Ambon Kuning, Morosebo, Rajah Sereh, and Raja Nangka. Whereas 4 accessions, namely Ambon Australia, Kepok Lebanon, Kidang and Raja Bakar, could not be analyzed for their kinship because the data collection of the banana generative phase had passed or had not yet entered the generative phase. Whereas 1 accession, namely Musa ornate, is believed to be included in the Rhodhoclamys section so that the genome type cannot be determined. Based on group analysis obtained 2 large groups at a scale distance of 20-23. At a smaller scale distance of 10 obtained a subgroup with a large number of members.